A Look at Uzbek Puppet Theater - Sayidolim, Khojaev; A’zamjon, Abdukhalilov (Journal of Learning on History and Social Sciences, 2024)
A child’s mind looking at the world with joy is an example of white paper, and his heart is equally innocent. In this sense, the issue of upbringing is a process that requires careful thought, diligence and a deep mental approach. It is not appropriate to write or choose a work without taking into account the age of children, and clearly distinguishing the age group of the audience is the most important component. Puppet theater and theater art in general have special educational, ideological and aesthetic functions in the education of our young generation. The article talks about puppet theater and the attention paid to this field in Uzbekistan.